Integrating omics reveals insights into tomato abaxial/adaxial leafy supplemental lighting - Jiang, Chengyao; Wu, Haolian; Zhang, Xiaoying; Liu, Jiaming; Li, Yushan; Song, Yu; Wang, Jue; Zheng, Yangxia (Frontiers in Plant Science, 2023)
Research revealed that the abaxial leafy supplemental lighting (AB) can significantly improve the net photosynthetic rate and stomatal conductance in the leaves of tomato plants compare to the adaxial leafy supplemental lighting (AD) method. However, the underlying regulatory mechanisms are still poorly understood. Here, we conducted AB and AD on tomato and assessed transcriptomic, and proteomic changes in leaves. The result showed that under the two supplemental lighting methods, a total of 7352 genes and 152 proteins were differentially expressed. Significant differences were observed in genes expression levels and proteins abundances across multiple pathways, mainly including cell process, metabolism process, biological regulation, environment information processing, genetic information processing, metabolism, and organismal systems. Additionally, we also found that some key genes that plant hormone signaling, light perception, photosynthesis, plant fitness, and promoting fruit ripening, have increased significantly, which can explain the effect of AB on plant growth and development. Finally, through the qPCR, we determined that AB mainly up-regulate a series of auxin-responsive genes or factors, auxin polarity transport genes, gibberellin synthesis genes, cell cycle regulator genes, sugar transporters, and fleshy fruit ripening genes. These results help us to understand plant light response mechanism and discover genes which contribute to efficient light energy utilization.